Pemodelan Employee Self Service Sistem Sebagai Penunjang Human Resources Department - Tanty Oktavia (Universitas Multimedia Nusantara, 2015)
The background of this research is based on the operational needs in human resources department to organize all the data and business processes that occur in this division. The role of the Human Resources division significantly to manage labor resources that contribute to the implementation of the organization’s operations. The objectives in this research is to build a model of information system that can support the operation in employee management system, which consists of employees’ personal data, attendance report, and document about employees competence. The method of this research refers to model lifecycle database [1]. The results achieved in this study was the establishment of a model of information systems and database design that can support the operations of the Human Resources Department that can be operated and controlled directly by the relevant employees, so that the operational process can be performed effectively and efficiently. Keywords: information system, human resources department, database lifecycle.